Unlocking the role of novel primary/di-amine oxidases in crop improvement: Tissue specificity leads to specific roles connected to abiotic stress, hormone responses and sensing nitrogen - Rakesh K. Upadhyay; Jonathan Shao; Jude E. Maul; Harry Schomberg; Avtar K. Handa; Daniel P. Roberts; Autar K. Mattoo (Journal of Plant Physiology, 2024)

Unlocking allelic variation in circadian clock genes to develop environmentally robust and productive crops - Sangam Lal Dwivedi; Luis Felipe Quiroz; Charles Spillane; Rongling Wu; Autar K. Mattoo; Rodomiro Ortiz (Planta, 2024)
Main conclusion Molecular mechanisms of biological rhythms provide opportunities to harness functional allelic diversity in core (and trait- or stress-responsive) oscillator networks to develop more climate-resilient and productive germplasm. Abstract The circadian clock senses light and temperature in day–night cycles to drive biological rhythms. The clock integrates endogenous signals and exogenous stimuli to coordinate diverse physiological processes. Advances in high-throughput non-invasive assays, use of forward- and inverse-genetic approaches, and powerful algorithms are allowing quantitation of variation and detection of genes associated with circadian dynamics. Circadian rhythms and phytohormone pathways in response to endogenous and exogenous cues have been well documented the model plant Arabidopsis . Novel allelic variation associated with circadian rhythms facilitates adaptation and range expansion, and may provide additional opportunity to tailor climate-resilient crops. The circadian phase and period can determine adaptation to environments, while the robustness in the circadian amplitude can enhance resilience to environmental changes. Circadian rhythms in plants are tightly controlled by multiple and interlocked transcriptional–translational feedback loops involving morning ( CCA1 , LHY ), mid-day ( PRR9 , PRR7 , PRR5 ), and evening ( TOC1 , ELF3 , ELF4 , LUX ) genes that maintain the plant circadian clock ticking. Significant progress has been made to unravel the functions of circadian rhythms and clock genes that regulate traits, via interaction with phytohormones and trait-responsive genes, in diverse crops. Altered circadian rhythms and clock genes may contribute to hybrid vigor as shown in Arabidopsis , maize, and rice. Modifying circadian rhythms via transgenesis or genome-editing may provide additional opportunities to develop crops with better buffering capacity to environmental stresses. Models that involve clock gene‒phytohormone‒trait interactions can provide novel insights to orchestrate circadian rhythms and modulate clock genes to facilitate breeding of all season crops.

Trade-offs of organic and organic-inorganic fertilizer combinations in tomato quality and yield: A global meta-analysis (1992–2021) - Jiahui Yang; Autar K. Mattoo; Yang Liu; Francis Zvomuya; Hailong He (European Journal of Agronomy, 2023)

Genomic analysis of the polyamine biosynthesis pathway in duckweed Spirodela polyrhiza L.: presence of the arginine decarboxylase pathway, absence of the ornithine decarboxylase pathway, and response to abiotic stresses - Rakesh K. Upadhyay; Jonathan Shao; Autar K. Mattoo (Planta, 2021)
Main conclusion Identification of the polyamine biosynthetic pathway genes in duckweed S. polyrhiza reveals presence of prokaryotic as well as land plant-type ADC pathway but absence of ODC encoding genes. Their differential gene expression and transcript abundance is shown modulated by exogenous methyl jasmonate, salinity, and acidic pH. Abstract Genetic components encoding for polyamine (PA) biosynthetic pathway are known in several land plant species; however, little is known about them in aquatic plants. We utilized recently sequenced three duckweed ( Spirodela polyrhiza) genome assemblies to map PA biosynthetic pathway genes in S. polyrhiza . PA biosynthesis in most higher plants except for Arabidopsis involves two pathways, via arginine decarboxylase (ADC) and ornithine decarboxylase (ODC). ADC-mediated PA biosynthetic pathway genes, namely, one arginase ( SpARG1 ), two arginine decarboxylases ( SpADC1 , SpADC2 ), one agmatine iminohydrolase / deiminase ( SpAIH ), one N-carbamoyl putrescine amidase (SpCPA) , three S-adenosylmethionine decarboxylases ( SpSAMDc1, 2, 3 ), one spermidine synthase ( SpSPDS1) and one spermine synthase ( SpSPMS1 ) in S. polyrhiza genome were identified here. However, no locus was found for ODC pathway genes in this duckweed. Hidden Markov Model protein domain analysis established that SpADC1 is a prokaryotic/biodegradative type ADC and its molecular phylogenic classification fell in a separate prokaryotic origin ADC clade with SpADC2 as a biosynthetic type of arginine decarboxylase. However, thermospermine synthase ( t-SPMS)/Aculis5 genes were not found present. Instead, one of the annotated SPDS may also function as SPMS, since it was found associated with the SPMS phylogenetic clade along with known SPMS genes. Moreover, we demonstrate that S. polyrhiza PA biosynthetic gene transcripts are differentially expressed in response to unfavorable conditions, such as exogenously added salt, methyl jasmonate, or acidic pH environment as well as in extreme temperature regimes. Thus, S. polyrhiza genome encodes for complete polyamine biosynthesis pathway and the genes are transcriptionally active in response to changing environmental conditions suggesting an important role of polyamines in this aquatic plant.

A tribute - Govindjee Govindjee; Brij Sawhney; Autar Mattoo (Plant Physiology Reports, 2021)

Features of a unique intronless cluster of class I small heat shock protein genes in tandem with box C/D snoRNA genes on chromosome 6 in tomato (Solanum lycopersicum) - Ravinder K. Goyal; Vinod Kumar; Vijaya Shukla; Rohini Mattoo; Yongsheng Liu; Sang Ho Chung; James J. Giovannoni; Autar K. Mattoo (Planta, 2012)

Nitric oxide donor-mediated inhibition of phosphorylation shows that light-mediated degradation of photosystem II D1 protein and phosphorylation are not tightly linked - Isabelle S. Booij-James; Marvin Edelman; Autar K. Mattoo (Planta, 2009)

D1-protein dynamics in photosystem II: the lingering enigma - Marvin Edelman; Autar K. Mattoo (Photosynthesis Research, 2008)

Sucrose non-fermenting 1-related protein kinase 2 (SnRK2): a family of protein kinases involved in hyperosmotic stress signaling - Vijaya Shukla; Autar K. Mattoo (Physiology and Molecular Biology of Plants, 2008)

A spectrum of genes expressed during early stages of rice panicle and flower development - Kumuda M. Kushalappa; Autar K. Mattoo; Usha Vijayraghavan (Journal of Genetics, 2000)

Enhancing biological nitrogen fixation: An appraisal of current and alternative technologies for N input into plants - Sivramiah Shantharam; Autar K. Mattoo (Plant and Soil, 1997)

Stimulation of growth and glucose catabolite enzymes by succinate in some thermophilic fungi - Anupam S. Wali; Autar K. Mattoo; V. V. Modi (Archives of Microbiology, 1978)